Christianity and Ecology in Historical and Ethical Contexts - Purwanto, Edi; Silalahi, Frans H. M. (Sekolah Tinggi Teologi Transformasi Indonesia, 2024)
Abstract: This study examines the historical relationship between Christianity and ecology, highlighting the dynamics between criticism and constructive engagement within Christian traditions regarding environmental issues. The research employs a systematic literature review to identify and analyze relevant studies. The findings reveal that Christianity, while often criticized for its contributions to ecological degradation, also holds significant potential to support ecological sustainability through its teachings and practices. A historical perspective illustrates how Christian doctrines advocate for a symbiotic relationship between humans and nature. This study further explores how Christian ethical principles can contribute to environmental conservation. Through a review of existing literature, the research demonstrates that Christian beliefs can encourage sustainable practices despite challenges in integrating religious values. These findings underscore Christianity's substantial potential to contribute to environmental conservation through a holistic ethical and spiritual approach. The implications of this study highlight the importance of engaging Christian communities in environmental movements through approaches rooted in religious values. By leveraging Christian ethical principles, ecological organizations, and policymakers can bridge the gap between spirituality and sustainable practices. Furthermore, this research creates opportunities for interdisciplinary dialogue between religion and environmental science, emphasizing the need for strategies that integrate religious values into global sustainability initiatives.